Prospective risk of fetal death with gastroschisis. (22nd November 2015) - Meyer, Michelle R.; Shaffer, Brian L.; Doss, Amy E.; Cahill, Alison G.; Snowden, Jonathan M.; Caughey, Aaron B.
Abstract: Objective: To evaluate the ongoing risk of intrauterine fetal demise (IUFD) in fetuses with gastroschisis compared to non-anomalous fetuses. Methods: This was a retrospective cohort study of all births in the United States in 2005–2006, as recorded in the National Center for Health Statistics natality database. Risk of IUFD in fetuses with gastroschisis was compared to non-anomalous fetuses, utilizing total at-risk fetuses as the denominator. Results: Risk of IUFD in fetuses with gastroschisis was 4.5%, compared to 0.6% in non-anomalous fetuses ( p  < 0.001). When controlling for gestational age and other confounders, the adjusted odds ratio for IUFD in fetuses with gastroschisis was 7.06 (95% CI: 3.33–14.96). After 32 weeks, risk of IUFD/ongoing pregnancy was greater at each week of gestation in fetuses with gastroschisis. Conclusions: Risk of IUFD for fetuses with gastroschisis is greater than in non-anomalous fetuses. This risk increases significantly after 32 weeks' gestation. Demographic variables are associated with higher rates of gastroschisis and ultimately IUFD. These data may be useful in consideration of timing of delivery.